Phylogenetic relationship and characterization of the complete chloroplast genome of Actinidia callosa var. strigillosa. Issue 3 (2nd July 2020) - Liu, Yaling; Xie, Xiaodong; Qi, Xiaoqiong; Zhong, Caihong; Li, Dawei
Abstract: Actinidia callosa var. strigillosa is one of the endangered Actinidia species scattering across mountain areas in southwest China. Here, we assembled and characterized the complete chloroplast (cp) genome sequence of A. strigillosa to provide genomic resources for its identification, conservation and utilization. The cp genome is 155, 957 bp in length, containing a pair of 23, 119 bp inverted repeat (IR) regions, which is separated by a large single copy region (LSC) of 89, 429 bp and a small single copy region (SSC) of 20, 290 bp. A total of 132 genes were annotated in this cp genome, including 83 protein-coding genes, 41 tRNA genes and 8 rRNA genes. The phylogenetic position of A. strigillosa based the cp genome data was sister to the group A. deliciosa and A. chinensis .